STRATEGI CITY BRANDING MELALUI GELARAN BUDAYA TARI SPARKLING SEBAGAI KOMUNIKASI PARIWISATA KOTA SURABAYA - Seyla Pratiwi Lestari; Glorya Agustiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
City branding is a strategy used by a city to build and communicate city’s strong positioning regionally and globally through tourism promotion. City branding of Surabaya is a form of Surabaya marketing communication tool in tourism, following the era where cities today rely on branding for packaging and promoting tourism in the city. Sparkling Surabaya promotional activities are carried out in various forms summarized in promotion and cooperation. Promotional material in the form of brochures, books, calendars, posters, pamphlets, stickers, photos, videos, maps, souvenirs, and free magazines can be found at the Tourist Information Center (TIC), hotels, and various other places that are easily accessible to the tourists. One of marketing communications tools of city branding arised nowadays is a cultural event, such as Sparkling Surabaya dance that expresses the city of Surabaya through motion as language of symbols. This study aims to determine the city branding strategy in an effort to promote tourism through the Sparkling dance culture event in Surabaya. The research method uses a qualitative approach with interviews and documentation as data collection techniques. The results of the research are useful for scientific development in the field of communication, especially for city government and the tourism industry in practical terms. Keywords: City Branding, Sparkling Surabaya Dance, Tourism Communication.